2021
DOI: 10.1042/ns20210008
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocytes in the aging brain

Abstract: More than half of the human brain volume is made up of white matter: regions where axons are coated in myelin, which primarily functions to increase the conduction speed of axon potentials. White matter volume significantly decreases with age, correlating with cognitive decline. Much research in the field of non-pathological brain aging mechanisms has taken a neuron-centric approach, with relatively little attention paid to other neural cells. This review discusses white matter changes, with focus on oligodend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 205 publications
(265 reference statements)
6
41
0
Order By: Relevance
“…These changes may be detrimental to OPC differentiation and myelin formation in the aged brain. Besides, other factors, including oxidative stress induced by vascular changes during aging and deregulation of glutamate neurotransmission in the aged brains may also play roles in age-related myelinogenesis decline ( Rivera et al, 2016 ; Bagi et al, 2018 ; Bors et al, 2018 ; Sams, 2021 ; Summarized in Figure 1 ).…”
Section: Mechanisms Of Inhibited Myelinogenesis During Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes may be detrimental to OPC differentiation and myelin formation in the aged brain. Besides, other factors, including oxidative stress induced by vascular changes during aging and deregulation of glutamate neurotransmission in the aged brains may also play roles in age-related myelinogenesis decline ( Rivera et al, 2016 ; Bagi et al, 2018 ; Bors et al, 2018 ; Sams, 2021 ; Summarized in Figure 1 ).…”
Section: Mechanisms Of Inhibited Myelinogenesis During Agingmentioning
confidence: 99%
“…For example, it was reported that OLs occupy about 75% of all glial cells in the neocortex of human brain (von Bartheld et al, 2016). More importantly, oligodendroglia lineage cells are undergoing dynamic changes during aging and that have been extensively reported recently (Stadelmann et al, 2019;Chapman and Hill, 2020;Sams, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Cellular senescence is apparent in astrocytes, microglia, and neurons of the midbrain which are neighbors to oligodendrocytes. There is accumulating evidence of senescencelike features in oligodendrocytes and their progenitors (Sams, 2021) with increasing age, but a clear demonstration of oligodendrocyte senescence in PD has yet to be shown. Senescence of oligodendrocytes has been reported in white matter lesions which are common in brain aging and are associated with dementia (Al-Mashhadi et al, 2015).…”
Section: Oligodendrocytesmentioning
confidence: 99%
“…Under the microscope, age-related degenerative abnormalities in myelin sheaths are revealed as myelin balloons (Feldman and Peters, 1998) and splits of the lamellae at the major dense line (Peters, 2002). Reasons for this are not clear, however, this could be a consequence of a complex of factors, such as reduced OPC differentiation (Sim, Zhao, Penderis and Franklin, 2002), differential vulnerability of oligodendrocytes to accumulation of DNA damage and oxidative stress (Tse and Herrup, 2017), altered lipid metabolism (LefĂšvre-Arbogast et al, 2021), and decreased nutrient and energy availability for myelinating cells (Sams, 2021). In addition, senescence-dependent abnormalities in myelin are often caused by a decrease in the expression level of various genes, including MBP, which serves as a robust indicator of brain age.…”
Section: Cell Biologymentioning
confidence: 99%